Particle swarm optimization: optimizing transportation cost problem / Siti Hafawati Jamaluddin ... [et al.] - Jamaluddin, Siti Hafawati; Mahmud, Norwaziah; Muhammat Pazil, Nur Syuhada; Ab Raji, Nurul Hidayah; Ghazali, Nurulain; Jusoh, Nordianah (UiTM Cawangan Perlis, 2017)
Transportation is literally defined as an act, process or instance of transporting or being transported. Many business organizations are relying on transportation in running their business. In these years, the transportation cost has increase from time to time and become a problem t o the organization to maintain the cost and profit. To overcome this problem, the optimization of cost is applied in order to make sure the business is in the right financial condition by finding the minimum cost of transporting a single commodity from a given number of sources to a given number of destinations. In this study the modified Particle Swarm Optimization is used to solve the Transportation Cost Problem (TCP) in finding the optimal solution of the amount of product transported with the minimum cost. The model of nonlinear cost function had been used throughout this study. As a result, the minimum cost of transportation is 340.69 with the amount of product transported 17, 15, 32, 16, and 20 following the arc A(x)={(1,5), (2,4), (2,6), (3,4), (3,5)} respectively.